Pengaruh Model Pembelajaran React Terhadap Kemampuan Berpikir Analisis Dan Minat Belajar Ditinjau Dari Level IQ - Dede Sulaeman; Yaya S. Kusumah; Endang Wahyuningrum (SJME (Supremum Journal of Mathematics Education), 2023)
This study uses a quantitative approach with quasi-experimental research. This study aims to 1) examine the effect of applying the REACT learning model on students' analytical thinking skills in terms of Intelligence Quotient (IQ) in class XI IPA. 2) Assess the effect of the application of the REACT learning model on students' learning interest in terms of IQ in class XI IPA. 3) Assessing the effect of the interaction of learning models and Intelligence Quotient (IQ) on students' analytical thinking skills in class XI IPA. 4) Assessing the effect of the interaction of learning models and Intelligence Quotient (IQ) on students' learning interest in class XI IPA. The population in this study were all students of class XI IPA SMA Islam Dian Didaktika Cinere Depok, samples were taken from two classes XI IPA with Cluster Random Sampling, while the design used was treatment by level design. The results show that 1) There is an effect of the application of the learning model on students' analytical abilities 2) There is no effect of the application of the REACT learning model on students' learning interest between the experimental and control groups. 3) There is an interaction between the REACT and Intelligence Quotient (IQ) learning models on students' analytical thinking skills. 4) There is no interaction between learning models and Intelligence Quotient (IQ) on students' learning interest.